Merekonstruksi Persekutuan Perdata Untuk Memenuhi Kebutuhan Praktek Hukum dan Bisnis Modern - Widjaja, Gunawan (LAW REVIEW, 2004)
"Maatschap", as regulated in Indonesian Civil Code, is the simplest form of Â "cooperation", whereby people ageree that they will jointly put on something (money, goods and or skill), manage, administer and then use it in order to obtain profit and distribute among them. Eventhough the regulation on "Maatschap " has been more than a century, its conception is still valid until today and can be used to explain modern business cooperation. This paper presents that the conception of "Maatschap " can be easily used to explain the relation within a Joint Operation and Loan Syndication.